2019
DOI: 10.1101/751834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic actin-mediated nano-scale clustering of CD44 regulates its meso-scale organization at the plasma membrane

Abstract: 23 24 25 26 27 28 29 2 Keywords: actomyosin, cartography, CD44, fluorescence emission anisotropy, formin, homo-30 FRET, meshwork, meso-scale organization, nanoclustering, nano-scale organization, plasma 31 membrane, single particle tracking 32 Abbreviations: ECD-extra-cellular domain; ICD-intra-cellular domain; ECM-extra-cellular 33 matrix; FRET -Forster"s resonance energy transfer; HA-hyaluronic acid; SPT-single particle 34tracking; DC-SPT-dual color single particle tracking 35 36 37 Abstr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Note the transient confinement zones and regions of free diffusion (marked by arrowheads) of one such protein, CD44 (b), which provides an appreciation of the influence of the multiple scales and modes of diffusion. The trajectory has been adapted from Reference 13…”
Section: Early Evidence Of Multiscale Organization Of Plasma Membranementioning
confidence: 99%
See 4 more Smart Citations
“…Note the transient confinement zones and regions of free diffusion (marked by arrowheads) of one such protein, CD44 (b), which provides an appreciation of the influence of the multiple scales and modes of diffusion. The trajectory has been adapted from Reference 13…”
Section: Early Evidence Of Multiscale Organization Of Plasma Membranementioning
confidence: 99%
“…Recent studies on the cell adhesion protein, CD44 have revealed such a hierarchical structuring of the membrane 13,61 . The extra‐cellular domain of CD44 binds the ECM component hyaluronic acid, 62 while its cytoplasmic domain binds to the actin cytoskeleton.…”
Section: Hierarchical Nano‐ and Mesoscale Organization Of A Cell Adhementioning
confidence: 99%
See 3 more Smart Citations